Development and Application Design of PALVoSoS Model For Junior High School Students With Intellectual Disability: A Case Study in Sidoarjo – Indonesia - et. al., Vendyah Trisnaningtyas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Persons with Intellectual Disabilities need help in overcoming their limitations to face life independently. This study aims to develop a project-based action learning model for junior high school students with intellectual disabilities to improve and practice life skills. The main product is designing an action learning project model that integrates learning at the junior high school level, especially vocational skills in making cookies and social skills in project learning. The development model uses the ADDIE model. The data analysis technique is divided into two stages. Analyzing data from expert test results on the developed product model, expert judgment data were analyzed using the Content Validity Index (CVI) formula. Second, data analysis of learning outcomes, namely vocational skills, makes cookies according to the number of students using the n-Gain test to determine the model's effectiveness on student learning outcomes. Based on expert validation and trial results, the resulting model follows the learning needs of junior high school students with intellectual disabilities. The results show that the action learning project model's design meets the requirements for learning, especially for junior high school students with intellectual disabilities. Overall, the authors conclude that learning with the vocational and social skills action learning project model can be implemented and can improve learning outcomes.